2013
DOI: 10.4103/0973-1296.113276
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and apoptotic effects of spanish honeys

Abstract: Background:Current evidence supports that consumption of polyphenols has beneficial effects against numerous diseases mostly associated with their antioxidant activity. Honey is a good source of antioxidants since it contains a great variety of phenolic compounds.Objective:The main objective of this work was to investigate the antiproliferative and apoptotic effects of three crude commercial honeys of different floral origin (heather, rosemary and polyfloral honey) from Madrid Autonomic Community (Spain) as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Honey has been extensively investigated for its effect on apoptosis in different types of cancer, with different proposed mechanisms of action. On a promyelocytic leukemia cell line (HL-60), it was observed that different types of honey (heater, rosemary and multifloral) were able to significantly increase the number of apoptotic cells in an ROS-independent manner [46]. A similar effect has been seen in renal carcinoma cells treated with Iranian multifloral honey [47].…”
Section: Effect Of Mh and Dmh On Apoptosismentioning
confidence: 69%
“…Honey has been extensively investigated for its effect on apoptosis in different types of cancer, with different proposed mechanisms of action. On a promyelocytic leukemia cell line (HL-60), it was observed that different types of honey (heater, rosemary and multifloral) were able to significantly increase the number of apoptotic cells in an ROS-independent manner [46]. A similar effect has been seen in renal carcinoma cells treated with Iranian multifloral honey [47].…”
Section: Effect Of Mh and Dmh On Apoptosismentioning
confidence: 69%
“…A number of other investigations also proposed apoptosis as a possible mechanism for observed antiproliferative effect. Treatment of human peripheral blood promyelocytic leukaemia cells (HL-60) with Spanish honey revealed that apoptosis plays a central role in the observed antiproliferative effect ( 54 ). Jaganathan and Mandal ( 55 ) also identified apoptosis as possible molecular mechanism responsible for honey inhibition of colon cancer cell growth.…”
Section: Resultsmentioning
confidence: 99%
“…Honey has also been reported to inhibit cell proliferation, induce apoptosis, alter cell cycle progression and cause mitochondrial membrane depolarization in many other forms of cancer including endometrial cancer cells [31], renal cell carcinoma [69], skin cancer cells (melanoma) [70], cervical cancer cell lines [37], human non-small cell lung cancer cells [71], mouth cancer cells (oral squamous cell carcinoma) and bone cancer cells (osteosarcoma) [72]. In a recently published article, Morales and Haza investigated the antiproliferative and apoptotic effects of three crude Spanish honey samples of different floral origin (polyfloral, heather and rosemary honey) and those of an artificial honey in HL-60, a human peripheral blood promyelocytic leukemia cell line [73]. The researchers reported that all the three honey samples induced apoptosis, in a concentration and time dependent-manner.…”
Section: Effects Of Honey On the Development And Progression Of Tumentioning
confidence: 99%
“…Several flavonoids and phenolics have been demonstrated to induce ROS in cancer cells [120]. However, a recent study revealed that while the concentrations of phenolic compounds play a key role in honey-induced HL-60 cell death, honey did not generate ROS and NAC (a potent antioxidant) did not prevent honey-induced cancer cell death [73]. This suggests that in spite of its high phenolic content, honey can still exert its anticancer effect via ROS-independent mechanism(s).…”
Section: Mechanisms Of the Antiproliferative Antimetastatic And Amentioning
confidence: 99%